A epistemologia de Gaston Bachelard nas publicações científicas: análise nas pesquisas em ensino de química (2000-2019) - Dorigon, Larissa (2021)
Considering the growing development of research in Science Education in last decades, the present study identified as state-of-the-art, presents a mapping of Brazilian academic research which addresses concepts of the epistemologist Gaston Bachelard in the Teaching of Chemistry. Therefore, it focuses on articles published in national journals in the field of Science Education classified as A1, A2 and B1 (quadrianium 2013 - 2016) by the "Banco da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior" (CAPES), in the time frame from 2000 to 2019 The objective is to establish an overview of this production, as well as point out trends and contribute to subsidize new research in the area and teaching of Chemistry in different educational contexts. The data analysis was carried out through the establishment of a priori descriptors, which highlight the main characteristics and trends in the analyzed works. The total number of selected articles was 17 works divided among 11 journals. Of these, most were produced by researchers from federal universities (66.66%). We also observed that 41.66% were produced by the Southeast region, followed by the South and Northeast regions with 12.5% each. The most investigated concept of chemistry was “atomic models” and the most recurrent Bachelardian concept was “epistemological obstacles”. The results show a certain advance in the area, but still with a reduced number of publications, considering its relevance and popularity at national and international level in Science Teaching at all educational levels.